Achieving ultra-high hardness of nanostructured Mg-8.2Gd-3.2Y-1.0Zn-0.4Zr alloy produced by a combination of high pressure torsion and ageing treatment. (October 2018) - Sun, W.T.; Qiao, X.G.; Zheng, M.Y.; Zhao, X.J.; Chen, H.W.; Gao, N.; Starink, M.J.
Abstract: A Mg-8.2Gd-3.8Y-1.0Zn-0.4Zr (wt%) alloy is subjected to a series of thermal and mechanical treatments involving solution treatment, artificial ageing to peak hardness, high pressure torsion (HPT) and a second artificial ageing. During HPT precipitates dissolve and during the final post-HPT ageing, the supersaturated solid solution decomposes and solutes segregate at grain boundaries. By employing this T6 + HPT + T5 treatment, the hardness increases to 156 ± 1 HV, which is much higher than that achieved by any other reported combination of thermal and thermo-mechanical processing of Mg alloys. The ultra-high hardness is due to the combined effects of solute segregation, grain refinement and high dislocation density. Graphical abstract: Unlabelled Image